"Now we shall reveal a little secret" first person plural and lyrical fluidity in the works of Amos Oz. Issue 2 (2nd July 2020) - Shemtov, Vered Karti
ABSTRACT: Throughout his career, Amos Oz explored different kinds of narrations that would enable him to capture both the story of individuals and the voices of the collective. The stories often presented a tension between the first person singular and the first person plural narration. In A Tale of Love and Darkness, Oz finally found a harmonious and comfortable way to speak and write in what I define as his "fluid I-Us" voice. I argue that a key to understanding the new and poetic I of A Tale of Love and Darkness is the 1999 book The Same Sea, which preceded the memoir. This book was the first fictional work by Oz to include his biographical self. In this book, Oz experimented with prose poetry, and with the narrative possibilities that the lyrical "I" can introduce into his work.